Factors affecting the perception and intention of Malaysian consumers to adopt mobile payment: an empirical study - Gan, Kok Lin (2018)
The study provides empirical evidence on the relationship between various factors which influence the mobile payment (m-payment) adoption decision among Malaysian consumers. Mpayment) has been the hot topic in town since end of 2000s’and has evolved from cashless transactions through portable devices such as laptops, tablets, mobile phone under electronic commerce (e-commerce) environment into mobile wallet (m-wallet) application powered by latest communication technology such as Near Field Communication (NFC), Quick Response Code (QR) and Radio-frequency Identification (RFID) at merchant Point of Sale (POS). The emergence of this cashless payment mode provides huge potentials for more efficient domestic economy by displacing traditional payment method like cash transactions. Despite the high penetration of internet usage and mobile phone ownership, adoption of m-payment is still low among local consumers. Therefore, the objective of this study is to examine the factors influencing m-payment adoption among consumers in Malaysia using a modified conceptual model. The constructs are adapted from various technology acceptance model such as Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT) and Unified Theory of Acceptance and Use of Technology (UTAUT). The research is carried out by applying online survey method to comprehend consumers’ perception on m-payment. Regression model is used to test the hypothesis on the influence of selected constructs (Perceived Usefulness (PU), Perceived Ease of Use (PEU), Trust, Social Influence, Compatibility, Security and Privacy and Perceived Cost) on local consumer m-payment adoption decision. The results revealed that PU, PEU, Trust and Compatibility has significant influence on local consumers’ intention to use mpayment where compatibility is the strongest predictor among them. The study recommended mpayment service providers to formulate strategy by focusing on four factors which has significant influence on m-payment adoption in order to maximise profit. On the other hand, regulators are advised to safeguard consumers’ rights to foster healthy m-payment environment in facilitating better economic growth in future.